THE INFLUENCE OF BRAND AWARENESS AND PRODUCT QUALITY ON REPURCHASE INTENTION OF MS GLOW SKINCARE PRODUCTS : MEDIATED BY BRAND TRUST - Alya Nurkhaliza; Syamsul Bachri; Elimawaty Rombe; Setiawan Mandala Putra (RADJA PUBLIKA, 2026)
This study aims to analyze the influence of brand awareness and product quality on repurchase intention of MS Glow skincare products with brand trust as a mediating variable. This study used a quantitative approach with a survey method of 120 students of the Faculty of Economics and Business, Tadulako University who have used MS Glow products. Sampling was carried out using a purposive sampling technique. Data analysis used Partial Least Squares Structural Equation Modeling (PLS-SEM) through the SmartPLS application. The results of the study indicate that brand awareness and product quality have a positive and significant effect on repurchase intention. In addition, brand awareness and product quality also have a positive and significant effect on brand trust. However, brand trust does not have a significant effect on repurchase intention and is unable to mediate the influence of brand awareness and product quality on repurchase intention. This study provides theoretical contributions to marketing studies as well as practical implications for companies in formulating marketing strategies that focus on strengthening brand awareness and improving product quality.